1999
DOI: 10.1007/bf03402073
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus (HSV)-Mediated ICAM-1 Gene Transfer Abrogates Tumorigenicity and Induces Anti-Tumor Immunity

Abstract: Background: Costimulatory and cellular adhesion molecules are thought to be essential components of antigen presentation in the immune response to cancer. The current studies examine gene transfer utilizing herpes viral amplicon vectors (HSV) to direct surface expression of adhesion molecules, and specifically evaluate the potential of a tumor-expressing intercellular adhesion molecule-1 (ICAM-1) to elicit an anti-tumor response. Materials and Methods: The human ICAM-1 (hICAMI) gene was inserted into an HSV am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…The indications of reduction of tumor progression associated with ICAM-1 overexpression in ovarian cancer, shown in the present study by using ATFs in vitro, is in line with results obtained upon transfecting ICAM-1 cDNA into various cancer cells: overexpression of the gene was associated with decreased tumorigenicity in vivo. [30][31][32][33][34][35] In fact, some studies show lower proliferation rates upon transfection of cancer cells (other than ovarian) with ICAM-1 cDNA and implantation into animal models. 32,33,35 The reduced growth in vivo has been ascribed to increased activation of immune response by the cells upon ICAM-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The indications of reduction of tumor progression associated with ICAM-1 overexpression in ovarian cancer, shown in the present study by using ATFs in vitro, is in line with results obtained upon transfecting ICAM-1 cDNA into various cancer cells: overexpression of the gene was associated with decreased tumorigenicity in vivo. [30][31][32][33][34][35] In fact, some studies show lower proliferation rates upon transfection of cancer cells (other than ovarian) with ICAM-1 cDNA and implantation into animal models. 32,33,35 The reduced growth in vivo has been ascribed to increased activation of immune response by the cells upon ICAM-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Production of cytokines in proximity to putative tumor antigens has been shown experimentally to result in antitumor immunity that prevents subsequent development of cancer. 12,[14][15][16][17][18][19][20][21][22] Recent animal studies from this laboratory have shown that neoadjuvant treatment of established, solitary liver tumors with modified, replication incompetent herpes simplex virus (HSV) encoding the interleukin-12 (IL-12) gene resulted in high levels of gene expression within the tumor and significantly reduced the incidence of tumor recurrence after resection. 23 However, this study showed no significant response of the parent tumor, which remains a major limitation of this treatment strategy.…”
mentioning
confidence: 99%
“…Transfection of the human ICAM-1 gene into various cancer cells lines using plasmid or viral vectors resulted in decreased tumorigenicity when injected into mouse or rat hosts (Burno et al, 1995;Wei et al, 1996;Uzendoski et al, 1997;D'Angelica et al, 1999;Kikuchi et al, 1999). Several lines of evidence demonstrate that this protection was due, at least in part, to activation of cellular immunity by ICAM-1 (Burno et al, 1996;Wei et al, 1996;Uzendoski et al, 1997;D'Angelica et al, 1999). Therefore, while more investigation is required to determine the significance of the reduced ICAM-1 expression levels in ovarian cancer, evidence from other models suggests that ICAM-1 gene transfer may be of value for the immunotherapy of ovarian cancer.…”
mentioning
confidence: 99%